(untitled) (Journal of Social Sciences Review, 2025)
The escalating need for sustainable urban mobility solutions amid concerns over climate change and fuel emissions makes the adoption of E-Bikes a critical area of study. This research investigates the psychological and cognitive factors that drive consumer Intention to Purchase E-Bikes (IPTEB), specifically examining how Environmental Awareness (EA), Consumer STEM Literacy (SL), and Perceived Technological Innovativeness (PTI) influence the perception of functional utility, operationalized as Perceived Technical Benefits (PTB). A quantitative study employing a cross-sectional design utilized Structural Equation Modeling (PLS-SEM) on data collected from 273 prospective E-Bike consumers in Multan, Pakistan. The structural model demonstrated high predictive power, explaining over 67% of the variance in the key endogenous constructs. All four hypothesized paths were supported, confirming that PTB is the overwhelming predictor of IPTEB (β= 0.820). Crucially, the antecedent variables influencing PTB ranked as follows: PTI (β= 0.373) was the strongest, closely followed by SL (β= 0.319), with EA exerting the weakest influence (β= 0.207). These findings suggest that while environmental concern provides motivation, the purchasing decision is fundamentally driven by rational, technology-based evaluations of product superiority, necessitating that manufacturers shift marketing strategy to focus on technical education and functional performance to maximize perceived value and accelerate adoption.